Variability in soil-water characteristic curve - Chin, Saw Bian (2014)
Soil-Water Characteristic Curve (SWCC) is an important property of unsaturated soil and is commonly used for estimation of other unsaturated soil properties such as permeability function, shear strength and volume change. SWCC variables such as the air-entry value and residual suction are commonly determined from the SWCC and referred in the description of the behaviour of shear strength and volume change of an unsaturated soil. The variability in SWCC may lead to uncertainty in the estimated unsaturated soil properties and SWCC variables. However, the variability in SWCC has not been extensively studied. Many factors may result in variability in SWCC. Variability in SWCC associated with experimental measurement was studied and explored in this project. The pressure plate was adopted as the measurement apparatus for this research and both mass and volume changes were monitored during the entire test. The time to determine equilibrium in water content was also studied. It was concluded that a criterion of less than 0.2% change in mass of soil specimen could be effectively used as indicator of equilibrium condition.